PENGARUH MODEL INKUIRI TERBIMBING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Sinta Wdiya Ningtias; Rahayu Soraya (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to determine the effect of the guided inquiry model on students' mathematical communication skills on the material of a two-variable system of linear equations. Population research was a class VIII SMP Negeri 3 Bandar Lampung. Subjects in this study were selected by cluster random sampling technique. Collecting data using observation techniques, questionnaires and tests of mathematical communication skills. The data analysis technique used is descriptive and inferential statistics.For students' mathematical communication ability test data, it consists of 4 essay questions covering 3 indicators of mathematical communication skills, namely, drawing (expressing ideas in the form of images, graphs or diagrams), written text (providing mathematical explanations in the correct language), and mathematical expressions. (make a mathematical expression). The data were analyzed quantitatively and qualitatively to get a comprehensive picture of students' mathematical communication skills.Based on the results of the t-test on the increase (N-gain) of mathematical communication skills obtained 0.049 <0.05. The results of the research and discussion show that the guided inquiry learning model is effective in improving students' mathematical communication skills.